Cancer Chemoprevention Using Nanotechnology-Based Approaches - Desai, Preshita; Thumma, Naga Jyothi; Wagh, Pushkaraj Rajendra; Zhan, Shuyu; Ann, David; Wang, Jeffrey; Prabhu, Sunil (Frontiers in Pharmacology, 2020)
Cancer research in pursuit of better diagnostic and treatment modalities has seen great advances in recent years. However, the incidence rate of cancer is still very high. Almost 40% of women and men are diagnosed with cancer during their lifetime. Such high incidence has not only resulted in high mortality but also severely compromised patient lifestyles, and added a great socioeconomic burden. In view of this, chemoprevention has gained wide attention as a method to reduce cancer incidence and its relapse after treatment. Among various stems of chemoprevention research, nanotechnology-based chemoprevention approaches have established their potential to offer better efficacy and safety. This review summarizes recent advances in nanotechnology-based chemoprevention strategies for various cancers with emphasis on lung and bronchial cancer, colorectal, pancreatic, and breast cancer and highlights the unmet needs in this developing field towards successful clinical translation.